Fenomena Living Islam dalam Sinetron Para Pencari Tuhan (Studi atas Tuntunan Sebelum dan Setelah Pernikahan dalam Sinetron Para Pencari Tuhan Jilid 3 Episode 19) - Muh Alwi (LP2M UIN Sunan Kalijaga, 2018)
This article attempts to present the various forms of living Islam (al-Qur’an and Hadith) found in the television program Para Pencari Tuhan (Those Who Seek God), particularly in season 3 episode 19. This study began with the assumption that every behavior is initiated based on an understanding (both textual and contextual) of religious texts, namely al-Qur’an and Hadith, including the various scenes presented in this television program. Subsequently, this article will discuss, as a focused study, matters of romance leading to marriage as experienced by Azam and Aya, Chelsea and Marni, Barong and Dara, and scenes of others who tried to involve themselves in the matter. Ultimately, this article presents various ways of living Islam found in the television program Para Pencari Tuhan; among them are the Hadith on fasting for the sake of Allah, Hadith on Khadijah’s special status, Hadith on the criteria of partners one should choose, Hadith on the prohibition of approaching a woman who is being proposed to, Hadith on the command for capable youth to get married, verses on polygamy, verses on the importance of atabayyun attitude, verses on helping each other, and verses on the benefits of marriage. The various Hadith and verses recorded in the scenes of the television program indicate that this program continues to hold a significant role in spreading Islamic teachings.